Major behavioral risk factors for road traffic injuries (One Health & Risk Management, 2021)
Introduction. Road traffic injuries are a major public health problem, ranking 8th in the leading causes of death and are forecasted to rank 5th by 2030 worldwide. Children, pedestrians, cyclists and the elderly remain among those most at risk of road traffic injuries.Material and methods. A specialized literature search was conducted within the main international databases, including: PubMed/MEDLINE, Google Scholar, and Research Gate, using a set of inclusion criteria. Data from references were extracted systematically into results tables, including: author/citation, study design, assessments/data, limitations, and key facts. Reported outcomes were compiled in narrative form.Results. Many researchers and scientists both in the country and abroad have studied road injuries. Authors of the studies used different methods and obtained obvious data about road traumas and major risk factors. Among the main causes of unintentional motor vehicle injuries were excessive speed, alcohol consumption while driving, mental disorder, drugs, and unsupervised children. There is an increasing incidence of road injuries among children, and most of the road traffic crashes involving children occur in May-September, between 11.00 and 18.00. The obtained results motivate the need to study this topic in depth, on separate age groups, and to propose specific prevention measures for each actor involved.Conclusions. There are many factors, which contributes to road crashes and related injuries, but those requires multisectoral involvement.